Indigenous peoples in Commonwealth countries : the legacy of the past and present-day struggles for self-determination - Burger, Julian (2013)
Looks at the colonial heritage as it affects indigenous peoples in the Commonwealth countries, some of contemporary struggles and situations that have marked the last years. Tries to understand why countries such as Australia, Canada and New Zealand were the last to accept that these peoples had a right to self-determination.